Fibre type changes in striated muscle of alcoholics. Issue 9 (September 1981) - Hanid, A; Slavin, G; Mair, W; Sowter, C; Ward, P; Webb, J; Levi, J
Abstract : Striated muscle from patients taking more than 80 g of alcohol each day shows selective atrophy of the type II fibres which are dependent on glycogenolytic pathways. This atrophy is associated with an excess of glycogen and lipid within the fibres and may represent a selective metabolic insult.